2017
DOI: 10.1111/jebm.12236
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and sleep: a systematic review of previous meta‐analyses

Abstract: Objective Conduct a systematic review of previous meta-analyses on exercise and sleep outcomes in adults and a meta-analysis of studies nested within these meta-analyses. Methods Meta-analyses of randomized controlled exercise interventions were included by searching nine electronic databases and cross-referencing. Dual-selection and data abstraction were conducted. Methodological quality of meta-analyses was assessed using AMSTAR and quality of evidence using GRADE. Random-effects models were used to pool r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
1
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(148 citation statements)
references
References 51 publications
(213 reference statements)
4
111
1
19
Order By: Relevance
“…As a core concept in sleep, sleep quality is largely subjective, so it is always evaluated using PSQI, a subjective self-report questionnaire, which is considered an accurate and effective method in clinical care and research, and is considered to be cheaper and more readily available than the gold standard measurement of sleep characteristicspolysomnography (35). Due to very few side effects, exercise, as a non-pharmaceutical and relatively safe activity, is widely chosen in clinical practice (36). It is reported that exercise can improve body composition and fitness, which is critical in enhancing sleep quality (37).…”
Section: Discussionmentioning
confidence: 99%
“…As a core concept in sleep, sleep quality is largely subjective, so it is always evaluated using PSQI, a subjective self-report questionnaire, which is considered an accurate and effective method in clinical care and research, and is considered to be cheaper and more readily available than the gold standard measurement of sleep characteristicspolysomnography (35). Due to very few side effects, exercise, as a non-pharmaceutical and relatively safe activity, is widely chosen in clinical practice (36). It is reported that exercise can improve body composition and fitness, which is critical in enhancing sleep quality (37).…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, promoting physical activity might be a low-cost and efficacious strategy. There is evidence that physical activity reduces sleep apnea [16], improves both overall sleep quality and subjective sleep, and diminished sleep latency [17,18]. Although it is generally accepted now that physical activity is associated with reduction of a wide range of sleep problems [18,19], it remains to be explored in more detail whether complying with the international guidelines of 150 min of moderate to vigorous physical activity per…”
Section: Introductionmentioning
confidence: 99%
“…For example, Babyak M [44] investigated 156 adult volunteers with major depressive disorder for 10 months, and found that increasing exercise time lowers depression relapse rates in comparison to that of the medication group. Apart from alleviating depression, exercise can also improve sleep quality, reduce morbidity of cardiovascular diseases, boost the immune system, and even promote neuronal plasticity [8][9][10][11][12]45], and thus have comprehensive benefits not only for the eyes, but the entire body.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) is an essential part of daily life, with PA guidelines in the US advising adults to set aside time for at least 150 min to 300 min of moderate intensity PA per week or 75 min to 150 min of vigorous intensity aerobic PA per week to stay healthy [7]. The health benefits of PA have been widely documented for both systemic and ocular diseases including boosting the immune system, improving sleep quality, reducing the incidence of cardiac-cerebral vascular events and is correlated with decreased anxiety and depression rates [8][9][10][11][12]. For eyes in particular, exercise can decrease the IOP [13] and decreasing IOP is associated with the magnitude of exercise [14].…”
Section: Introductionmentioning
confidence: 99%